Synthesis of Pyrazolines via (3+2) Cycloaddition of Nitrile Imines and N-Silyl Enamines - Yun, Sooyeon; Cao, Vinh Do; Shin, Sooah; Ahn, Byungin; Joung, Seewon (Synthesis, 2025)
The synthesis of tricyclic fused pyrazolines from N-silyl enamines and nitrile imines is presented. N-Silyl enamines are an emerging class of enamines that can be used as free enamine surrogates. The N-silyl enamines, prepared from readily available isoquinolines, underwent (3+2) cycloaddition with a wide range of nitrile imines to form the corresponding pyrazolines in moderate to good yields. This cascade protocol entailed the in situ utilization of both N-silyl enamine and nitrile imine intermediates.
Keywords: N-silyl enamines; B(C6F5)3; (3+2) cycloaddition; pyrazolines; nitrile imines